UMKM PARTICIPATION IN HALAL INDUSTRY: THE LEGAL FRAMEWORK AND OPPORTUNITIES - Siregar, Fitri Ana; Razali, Khairil (Universitas Islam Negeri Ar-Raniry, 2022)
Economic growth is an indicator used to see development success in a country, including Indonesia. The Covid-19 pandemic has a significant impact on economic growth, such as a decline in each quarter of 2020. It also affects the income and level of consumption of the community. UMKM, as the spearhead of economic affairs, can certainly provide solutions to the problems faced. The tendency of the halal industry, especially in halal products, is currently experiencing a panic, where all products must have a halal certificate. This study aims to analyze the potential of halal-based UMKM on the economy after the Covid-19 pandemic. The research method is qualitative with a literacy approach, referring to the findings that correlate with the studied variables. The result of this research is that halal-based UMKM provides economic improvement. The population of Muslims in Indonesia reached 229.62 million people, and it has an impact on the level of consumption of foods and drinks labelled as halal, especially during a pandemic. The tendency that occurs determines consumption in society. Therefore, halal-based UMKM have the potential to improve the economy during the pandemic and post Covid-19 pandemic.